Verification of the operating condition of stationary industrial gearbox through analysis of dynamic signal, measured on the pinion bearing housing. (January 2017) - Baron, Petr; Kočiško, Marek; Blaško, Lukáš; Szentivanyi, Patrik
Abstract: In order to ensure quality maintenance of rotary machinery, proper interpretation of the malfunction causes is required. The behaviour of the mechanical components of the machinery is often reflected in vibrations responding to the action of internal as well as external forces. The paper focuses on the issues of the application of the tools of technical diagnostics in verification of the technical condition of two-stage bevel-spur gearbox operating in difficult conditions of paper industry. Pinion bearing dismantled from malfunctioned gearbox was analysed. After repair, measurements were performed in order to determine the dynamic properties of the bearings. The values measured on the machine after repair were compared in two operating modes - depending on motor rotation speed. The acquired values of dynamic parameters and temperature (after repair) were in correlation to the condition found on the malfunctioned bearing (after dismantling form the malfunctioned gearbox).